1986
DOI: 10.1111/j.1469-1809.1986.tb01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Hunter Syndrome: carrier detection, new mutations, segregation and linkage analysis

Abstract: We have investigated 31 families segregation for Hunter Syndrome in order to advance our understanding of the genetics of this disease. The hair root test for the diagnosis of carriers of Hunter Syndrome was improved by the adoption of a new diagnostic index that distinguishes between carrier and normal females better than previous methods of analysis. One hundred and eleven female relatives of the affected children were tested by such procedures. This showed that seven out of 31 mothers were not carriers (22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The IDS gene was mapped to chromosome Xq28 by a combination of linkage studies (Upadhyaya et al, 1986;Chase et al, 1986; LeGuern et al, 1990) and cytogenetic analysis of an affected female patient (Mossman et al, 1983). IDS cDNA was sequenced (Wilson et al, 1990) and subsequently the intron-exon structure was determined by Flomen et al (1993) and Wilson et al (1993) and was found to consist of nine exons spanning approximately 24 Kb of genomic DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The IDS gene was mapped to chromosome Xq28 by a combination of linkage studies (Upadhyaya et al, 1986;Chase et al, 1986; LeGuern et al, 1990) and cytogenetic analysis of an affected female patient (Mossman et al, 1983). IDS cDNA was sequenced (Wilson et al, 1990) and subsequently the intron-exon structure was determined by Flomen et al (1993) and Wilson et al (1993) and was found to consist of nine exons spanning approximately 24 Kb of genomic DNA.…”
Section: Introductionmentioning
confidence: 99%
“…There was significant heterogeneity among samples in both the estimation of p (x2= 12-04, 4 df, p<0025) and the estimation of x when p was kept constant (X2=13-63, 4 df, p<0-01). In both cases the heterogeneity was the result of the substantial contribution of the Z sample (table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The ax r and rx s tables for the Hunter families from the GDR are reported in table 1, along with those of 36 families collected in sample Y,' of 19 families collected in sample T,5 of nine families collected in sample Z,6 and of 31 families collected in sample C. 4 The maximum likelihood value of in the M sample was estimated as 0-88. Accordingly, our best estimates of prevalence and incidence in the GDR become 4-8 and 9-4 per million male live births, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…When this clone was used to screen a group of Hunter patients, about one third were found to have deletions or rearrangements of the gene; the remaining subjects had either small deletions or point mutations which could not be analysed by the techniques Genetic counselling of female relatives in families with an affected male Huntcr patient is hampered by tcchnical difficulties. The estimation of the levels of the specific lysosomal enzyme cu-ISS in hair root cells provides clear results in most cases, but does not reveal the cause of the a-ISS deficiency (35).…”
Section: Hunter Syndrome: Carrier Detectionmentioning
confidence: 96%
“…In the course of a previous study, female relatives of the patient had been testcd to assess their carrier status using the hair root assay (35). The mother, one sister, an aunt and a cousin were found to be carriers of the abnormal gene, while other relatives, including another sister, had normal a-ISS enzymatic activity.…”
Section: Hunter Syndrome: Carrier Detectionmentioning
confidence: 99%